Glasgow Coma Scale: Linguistic-Cultural Adaptation of the Russian Version - M. A. Piradov; N. A. Suponeva; Yu. V. Ryabinkina; E. V. Gnedovskaya; K. A. Ilyina; D. G. Yusupova; A. A. Zimin; L. A. Legostaeva; E. G. Yazeva; I. S. Bakulin; A. B. Zaitsev; N. V. Polekhina; et al. (Неотложная медицинская помощь)
INTRODUCTION Determination of the degree of depression of consciousness in patients with brain damage upon admission to the intensive care unit and intensive therapy is a primary task. In order to carry out a quick and at the same time sufficiently complete assessment of this kind, in 1974 neurosurgeons Graham Teasdale and Bryan Jennett from the University of Glasgow developed an algorithm consisting of a sequential series of tests in the form of eye opening, speech and motor responses, called Glasgow Coma Scale. This scale has received worldwide recognition and for many decades has been the main one for determining the state of consciousness in the most severe patients with brain damage. The absence  of a validated version of this scale complicates its application in Russia, and the use of currently available versions that have not passed all the necessary  stages of validation distorts the originally intended meaning of the scale and does not allow obtaining reliable clinical results when examining patients with acute impairment of consciousness.AIM OF STUDY Development of the official Russianlanguage version of the Glasgow Coma Scale, taking into account linguistic and cultural  characteristics (1st stage of the validation study).MATERIAL AND METHODS The staff of Center for Validation of Health Status Questionnaires and Scales in Russia, Research Center of Neurology obtained consent from G. Teasdale to validate Glasgow Coma Scale in Russia. Two Russianspeaking professional certified translators in the field of  medicine performed a direct translation of the original Englishlanguage scale, and a reverse translation was carried out by native speakers with a medical education. Pilot study was performed in 15 patients with acute impairment of consciousness, two meetings of the expert committee were held (before and after pilot study).RESULTS Based on the results of the first meeting of the expert commission, a linguistic and cultural adaptation of the text of the scale was carried out. During the pilot testing of the researchers did not have difficulties in understanding and interpreting instructions. As a result, the second meeting of the expert commission was held and the final Russianlanguage version was approved, which is presented in this article and is available on the website of Center for Validation of Health Status Questionnaires and Scales in Russia, Research Center of Neurology.CONCLUSION For the first time, the Russian language version of the Glasgow Coma Scale was officially presented and recommended for use both in clinical and research practice in Russia and other Russian speaking countries. The next publication will highlight the result of assessing the psychometric properties (reproducibility, interexpert agreement and sensitivity) of the Russianlanguage version of the scale.